2020
DOI: 10.1002/ehf2.12884
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and natural history of wild‐type transthyretin amyloid cardiomyopathy in Japan

Abstract: Aims The focus on wild-type transthyretin amyloid cardiomyopathy (ATTRwt-CM) is increasing because of novel treatment options. There is currently no report on a large number of Japanese patients with ATTRwt-CM. The study aimed to examine the characteristics and prognosis of ATTRwt-CM in Japan. Methods and results Consecutive patients (78.5 ± 6.4 years old at diagnosis) with ATTRwt-CM diagnosed at Kumamoto University Hospital between December 2002 and December 2019 were retrospectively reviewed. Data, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 30 publications
1
57
1
Order By: Relevance
“…These data are consistent with prior observational studies in patients with ATTR‐CM, which have demonstrated the poor prognosis of the disease, both for patients with ATTRwt ( Table S1 ) and for patients with ATTRv ( Table S2 ). 7 , 10 , 16 , 17 , 18 , 19 , 20 As in ATTR‐ACT, observational studies have shown that patients with ATTRv tend to have more severe disease, and poorer survival, than patients with ATTRwt. Collectively, these studies reveal a consistent population of patients with ATTRwt, the majority (>80%) male, aged approximately 75 years, with elevated NT‐proBNP/BNP levels and preserved or mildly reduced ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data are consistent with prior observational studies in patients with ATTR‐CM, which have demonstrated the poor prognosis of the disease, both for patients with ATTRwt ( Table S1 ) and for patients with ATTRv ( Table S2 ). 7 , 10 , 16 , 17 , 18 , 19 , 20 As in ATTR‐ACT, observational studies have shown that patients with ATTRv tend to have more severe disease, and poorer survival, than patients with ATTRwt. Collectively, these studies reveal a consistent population of patients with ATTRwt, the majority (>80%) male, aged approximately 75 years, with elevated NT‐proBNP/BNP levels and preserved or mildly reduced ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…The approximately one‐third mortality over 30 months in patients with ATTRwt in ATTR‐ACT was also consistent with the approximately one‐quarter to one‐third mortality over 24–48 months in observational studies. 7 , 10 , 16 , 17 , 18 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once cleaved in these mechano-enzymatic conditions, they also readily form amyloid fibrils in vitro at physiological pH and salt concentration 26 , yielding fibrils with very similar morphology and biophysical properties to natural ex vivo human ATTR amyloid fibrils 26 , 40 . Clinical wild-type ATTR amyloid presents almost exclusively with cardiac amyloidosis, which is often presaged by carpal tunnel syndrome due to deposits in the flexor retinaculum and/or flexor tenosynovium 70 , and is usually accompanied by amyloid in skeletal muscle 14 . The accumulation of amyloid in these sites of mechanical stress is consistent with a mechano-enzymatic mechanism for amyloid formation.…”
Section: Discussionmentioning
confidence: 99%
“…Age, hs‐cTnT concentration, BNP concentration, and eGFR are conventional prognostic factors in patients with ATTR‐CM. 4 , 15 Therefore, these variables and LASr were forced into multivariable Model 1. Age and three echocardiographic findings (LAVI, pLASRct, and LASr) were forced into multivariable Model 2.…”
Section: Methodsmentioning
confidence: 99%